Transition Status of Land Property Values Based on State Land to Be Justice (Study on The Granting of Compensation of Land Development Projects Pemalang - Batang Toll Road) - Anisa Humaida; Umar Ma'ruf (Jurnal Akta, 2018)
Practice transitional land rights usually involve communities affected by development projects such as those in Pemalang-Batang toll road construction project. The method used in this research is juridical empirical method. This research is descriptive. With the research that is descriptive, it can be analyzed and compiled the data collected, so that it can be concluded that a general nature, as well as giving a clear picture of the role of the Notary in the transaction of land acquisition for the construction site of Pemalang-Batang Toll Road (PBTR) , The field data were analyzed qualitatively and literature that only retrieve data related to the issues discussed. Legal uncertainty for public land needs to be a concern for the government. As for efforts to be made, among others, regulatory arrangement to produce quality legal regulations, Based on Presidential Decree Number 36 Of 2005 and Presidential Decree No. 65 of 2006, there are two points that are important in the release of land property rights to state land. The process of transitional status of land property rights to state land to development projects Pemalang-Batang toll road has reached 99.21% starting in October 2017. This indicates that the transition process is almost completed and the soil needs to be studied further whether the operation has been fulfilling the principle of justice, Based on Presidential Decree Number 36 Of 2005 and Presidential Decree No. 65 of 2006, there are two points that are important in the release of land property rights to state land. The process of transitional status of land property rights to state land to development projects Pemalang-Batang toll road has reached 99.21% starting in October 2017. This indicates that the transition process is almost completed and the soil needs to be studied further whether the operation has been fulfilling the principle of justice, Based on Presidential Decree Number 36 Of 2005 and Presidential Decree No. 65 of 2006, there are two points that are important in the release of land property rights to state land. The process of transitional status of land property rights to state land to development projects Pemalang-Batang toll road has reached 99.21% starting in October 2017. This indicates that the transition process is almost completed and the soil needs to be studied further whether the operation has been fulfilling the principle of justice.Keywords: Switching Status of Land; Land Property; State Land.